Construção explícita de métricas de Einstein-Finsler com curvatura flag não constante - Silva, Carlos Antonio Freitas da (2015)
In this dissertation we will study Finsler Geometry. In particular, we will study Randers Geometry that which can be viewed as Riemannian Geometry with a pertubation. Furthermore Randers metrics are also obtained as solution to Zermelo’s Navigation Problem. We will also use classification theorems of Randers metrics of constant flag curvature and Einstein Randers metrics in terms of Zermelo’s Navigation Problem. Using Randers metrics we are going to construct a 3-parameter family of Einstein-Finsler metrics with non-constant flag curvature and to get such family we use a Killing vector field and a Riemannian metric which is the Hawking Taub-NUT metric.